Subcapsular liver hematoma.: arteriographic diagnosis - Valls, Alberto; Matteucci, Pablo; Grillo, Bartolomé (Cirugía del Uruguay, 1978)
A patient had developed a subcapsuJ'ar Jiver hematoma as a result of trauma and this diagnosis was confirmed through X-ray study; selective arteriography showed typical arterial rejection images of vascular branch arteriolocapi!J'ary; times indicated that the cavity was occupied by a hematoma.